Analisis Faktor yang Mempengaruhi Keberhasilan Kerjasama Kontraktor dengan Pemasok Ready Mix Pembangunan PSU Jalan Penghubung pada Perumahan Skala Besar Kota Jambi - Asri, Budi Irwan; Wahyudi, Wahyudi; Martalius, Martalius (Universitas Batanghari Jambi, 2024)
Limited resources require contractors to cooperate or collaborate to be able to participate in the connecting road construction project in large-scale housing in Jambi City, the quality requirements of the concrete used require contractors to use ready mix concrete. Ideally, cooperation is the most innovative way to anticipate limited resources and reduce disputes. However, obstacles such as weak cooperation, lack of trust, and ineffective communication are caused by different backgrounds and it is not easy to unite in a team. Therefore, knowledge of the factors leading to the success of cooperative relations is required. Based on this. The purpose of this study is to identify the dominant factors and factors that influence the success of contractor cooperation with ready mix suppliers for the construction of connecting road PSUs in large-scale housing in Jambi City, as well as determining efforts to improve the success of cooperation between contractors and ready mix suppliers for the construction of connecting road PSUs in large-scale housing in Jambi City. The analysis method is carried out with the application of the Statistical Package for the Social Sciences (SPSS). This study used quantitative methods by distributing questionnaires to respondents. The results of the research conducted there are 7 factors that influence the success of contractor cooperation with ready mix suppliers for the construction of PSU connecting roads in large-scale housing in Jambi City, namely communication factors, trust factors, commitment factors, role and responsibility factors, management support factors, information and resource factors, and common goal factors.